Surface-functionalized hollow polymer microsphere as well as preparation method and application thereof
Through soap-free emulsion polymerization method and organic solvent swelling treatment, hollow polymer microspheres with good spherical shape and uniform particle size were prepared, which solved the problems of easy damage on the surface of microspheres and limited functional groups in the prior art, and achieved high efficiency Functional microsphere preparation, suitable for applications in many high-precision fields.
Patent Information
- Application Number
- CN202310873572.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-07-17
AI Technical Summary
The existing hollow polymer microsphere preparation methods are complex, resulting in the surface of the microspheres being easily damaged, irregular in shape, uneven in particle size, and limited functional groups, making it difficult to perform biological coupling and chemical modification.
The monodispersed solid polymer microspheres were prepared by soap-free emulsion polymer polymer polymer microspheres, and then hollow polymer microspheres were obtained by swelling of organic solvents. The hydrophilic epoxy functional groups were used to preferentially distribute the outer side of the microsphere during the polymerization process, which was hydrophobic. Functional groups are distributed internally, controlling the polymerization tendency and reaction conditions to achieve a hollow structure with uniform particle size and complete surface.
Hollow polymer microspheres with good spherical shape, no recesses on the surface, uniform particle size and high load capacity are obtained, with high surface area and low density, and are suitable for applications in many high-precision fields.
Smart Images

Figure CN119320510A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a surface functionalized hollow polymer microsphere and a preparation method and application thereof. Background Art
[0002] Polymer microspheres are currently important functional polymer materials. Early polymer microspheres were mainly used in bulk product fields such as coatings, plastic additives, building materials, and paper surface processing. In recent years, the application fields of polymer microspheres have continued to expand, and research in the fields of biomedicine and biochemical engineering has been particularly popular, including the embedding of toxic or bioactive substances, the loading of fluorescent dyes, and the immobilization of enzymes. As the application of polymer microspheres has shifted from bulk products to high-tech fields, higher requirements have been placed on the performance of polymer microspheres, including microsphere particle size and monodispersity, thermal stability, and resistance to organic solvents. However, traditional polymer microspheres are mostly solid structures. In order to expand the application range of polymer microspheres, it is necessary to study hollow polymer microspheres. Compared with traditional solid polymer microspheres, hollow polymer microspheres have the advantages of low density and large specific surface area, and can adsorb or load more active substances. They have broad application prospects in the control and release of drugs, energy storage materials, and the loading of fluorescent dyes. Therefore, the design and controllable synthesis of hollow polymer microspheres has important scientific significance and practical value.
[0003] At present, the traditional preparation methods of hollow polymer microspheres mainly include self-assembly method, emulsion method, template method, etc. Among them, the template method has become the most commonly used method for preparing hollow microspheres due to its many advantages such as good predictability, high repetition rate and stable performance. Among them, the template method for preparing hollow polymer microspheres is divided into soft template method and hard template method. The soft template method uses soft vesicles or micelles as templates to make the polymerization reaction occur on the surface of the template to prepare hollow polymer microspheres. However, the hollow polymer microspheres synthesized by this method have irregular shapes and usually uneven particle size distribution; in addition, when preparing hollow polymer microspheres by the soft template method, a large amount of surfactants need to be added, which limits the application of the soft template method; while the hard template method uses stable polymers or inorganic nanoparticles as cores, the polymerization reaction occurs on the surface of the template, and finally the template is removed by calcination or solvent etching.
[0004] At the same time, the preparation process of hollow microspheres prepared by the prior art is relatively complicated, and the surface structure of the microspheres is easily damaged during the preparation process, such as causing depressions on the surface of the microspheres or forming large holes, which can easily lead to leakage of internal functional substances or direct contact with the external environment. In addition, the functional groups on the surface of the prepared microspheres are limited, making it difficult to carry out functional designs such as bioconjugation and chemical modification according to the application target.
[0005] Therefore, providing a surface-functionalized, internally hollow, monodisperse polymer microsphere and a preparation method thereof is a technical problem that needs to be solved urgently in the art. Summary of the invention
[0006] The purpose of the present invention is to provide a surface functionalized hollow polymer microsphere and a preparation method and application thereof. The present invention first prepares monodisperse solid polymer microspheres by adopting a soap-free emulsion polymerization method, and then uses an organic solvent to swell the microspheres to obtain hollow polymer microspheres. The prepared product has good sphericity, no surface depressions, uniform particle size, high load capacity, and has the characteristics of high surface area and low density.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing surface functionalized hollow polymer microspheres, comprising the following steps:
[0009] (1) stirring styrene, functional monomers, initiators, active ingredients and deionized water to obtain an emulsion for standby use;
[0010] (2) The emulsion is swollen with an organic solvent, and the precipitate obtained after centrifugation is the surface functionalized hollow polymer microspheres.
[0011] The functional monomer used in the present invention has a hydrophilic epoxy functional group. During the soap-free emulsion polymerization, the hydrophilic functional group is preferentially distributed on the outside of the microsphere, while the hydrophobic functional group is mostly distributed inside the microsphere. Among them, the hydrophilic poly(glycidyl methacrylate) is basically not dissolved in an organic solvent, mainly because the glycidyl methacrylate on the outside of the microsphere undergoes cross-linking during the continuous reaction, while the polystyrene distributed inside is very easily dissolved in an organic solvent.
[0012] In a conventional polymerization reaction, two monomers tend to copolymerize randomly, resulting in more surface damage to the microspheres during the swelling process of the organic solvent, and failure to form a high-quality hollow structure. However, the present invention adds active ingredients to the reaction solution of styrene and glycidyl methacrylate, which can change the polymerization tendency between the monomers, that is, more polyglycidyl methacrylate tends to be distributed outside the microspheres, while more polystyrene tends to be distributed inside the microspheres, and the morphology of the microspheres does not change substantially during the swelling process. Furthermore, by controlling the reaction conditions, functionalized hollow polymer microspheres with uniform particle size and monodispersity can be obtained.
[0013] Preferably, the mass ratio of the active ingredient to the deionized water in step (1) is 0.003-0.3:100;
[0014] The volume ratio of the styrene, the functional monomer and the deionized water is 3-10:1.2-6:100;
[0015] The mass ratio of the initiator to the deionized water is 0.05-0.4:100.
[0016] Among them, the polymer chain of the microsphere without adding functional monomers is a linear structure, which is difficult to stably exist in a high concentration of organic solvents; however, by adding a relatively high amount of functional monomers in the present invention, the synthesized polymer microspheres can stably exist in a high concentration of organic solvents for a long time, and the amount of functional monomers can make the microspheres in a hollow structure at a suitable ratio. Increasing the amount of functional monomers will reduce the hollowness of the microspheres, and significantly reducing the amount of functional monomers will cause the microspheres to be damaged or dissolved to a greater extent in the organic solvent;
[0017] Moreover, the present invention can obtain hollow polymer microspheres with intact surfaces after swelling by adding an appropriate amount of active ingredients to the reaction solution. At the same time, increasing the amount of active ingredients will also increase the hollowness of the microspheres, but excessive active ingredients will cause adhesion during the preparation and swelling of the microspheres.
[0018] Preferably, the preparation method is carried out in an inert gas atmosphere.
[0019] Preferably, the reaction temperature in step (1) is 63-75°C, the reaction time is 4-16h, and the stirring speed is 150-600rpm.
[0020] Preferably, the reaction temperature in step (1) is 70°C.
[0021] Preferably, the active ingredient in step (1) comprises mineral salts and / or biomacromolecules;
[0022] The functional monomer is glycidyl methacrylate;
[0023] The initiator is any one of potassium persulfate, sodium persulfate and ammonium persulfate.
[0024] Preferably, in step (2), the volume ratio of the emulsion to the organic solvent is greater than 1, and the swelling time is greater than 1 min.
[0025] Preferably, in step (2), the volume ratio of the emulsion to the organic solvent is greater than 3, and the swelling time is greater than 5 min.
[0026] In the present invention, the time required for swelling is shorter, the higher the amount of organic solvent used, the greater the hollowness of the microspheres, the faster the swelling rate, and the longer the swelling time, the less obvious difference in the morphology of the microspheres.
[0027] Preferably, the organic solvent in step (2) is at least one of tetrahydrofuran, acetone, ether, ethyl acetate, cyclohexane, toluene, xylene and trimethylbenzene.
[0028] Preferably, the mineral salt includes at least one of calcium salt, phosphorus salt, magnesium salt, potassium salt, sodium salt, iron salt, zinc salt, copper salt, manganese salt, iodine salt, selenium salt and molybdenum salt;
[0029] The biomacromolecules include at least one of amino acids, nucleotides, polysaccharides, vitamins and proteins.
[0030] Preferably, the prepared hollow polymer microspheres are centrifuged to discard the supernatant, and then washed and centrifuged alternately with water, ethanol or ethanol / water mixture.
[0031] A surface functionalized hollow polymer microsphere obtained by the preparation method described above.
[0032] Preferably, the particle size of the hollow polymer microspheres is 100-1000 nm.
[0033] The surface functionalized hollow polymer microspheres obtained by the preparation method described above are used in the preparation of catalysts, thermal insulation and sound insulation materials, optoelectronic materials, magnetic materials, and drug microcapsule materials.
[0034] The surface functionalized hollow polymer microspheres obtained by the preparation method described above are used in the fields of aerospace, oil extraction, ocean exploration, communications, ships, automobiles, rail transportation, building materials, chemicals, electronics, medical treatment, environmental protection, cosmetics, and sporting goods.
[0035] The controllable preparation of high-quality hollow polymer nanospheres fills the gap in this research field. The proposal of this method is of epoch-making significance. It will not only open up the exploration of the scientific principles behind subtle preparation methods, reveal new mechanisms for the synthesis of polymer materials and open up new paths, but will also greatly promote the rapid development of multiple bottleneck technologies.
[0036] It is noteworthy that the hollow polymer microspheres prepared by the present invention have good sphericity, no depressions on the surface, uniform particle size, high surface area and low density, etc. The size of the hollow microspheres is at the nanometer scale, and the application range is wider than that of micrometer hollow microspheres. They have high strength, heat preservation, fire prevention and corrosion resistance, insulation, wear resistance, good fluidity, and easy filling. Therefore, they have broad application prospects in the fields of catalyst carriers, thermal insulation and sound insulation materials, optoelectronic materials, magnetic materials, drug microcapsule materials, aerospace, oil extraction, marine exploration, communications, ships, automobiles, rail transportation, building materials, chemicals, electronics, medical treatment, environmental protection, cosmetics, sporting goods, etc., for example:
[0037] (1) Application in aviation, aerospace and submarine materials
[0038] Adding nanometer-scale hollow polymer microspheres to the matrix resin can effectively reduce the material density while maintaining the strength of the material, and can be applied to special functional materials such as aviation, aerospace and submarines. For example, fuselage, spacecraft wall panels, roof panels, electronic components, switch equipment, etc.
[0039] (2) Application in oil extraction
[0040] Hollow polymer nanospheres have low density, high strength and are non-absorbent, and have irreplaceable advantages in ultra-deep wells and ultra-low density cement slurries. Drilling fluids containing hollow polymer nanospheres have good rheological properties and inhibition, a wide adjustable density range, uniform and stable dispersion, and can ensure the consistency of wellbore density. At the same time, they solve the problem that measurement while drilling instruments cannot effectively transmit signals in multiphase flow. In addition, hollow polymer nanospheres can be combined with radionuclides and play an important role in drilling and mining applications.
[0041] (3) Application in automobile lightweighting
[0042] By replacing traditional fillers, hollow polymer nanospheres can reduce the weight of molded parts without sacrificing strength or aesthetics. The application of hollow polymer nanospheres in lightweight automobiles mainly includes the following ways: (a) hollow polymer nanospheres are used in automobile modified engineering plastics; (b) hollow polymer nanospheres are used in low-density SMC (Sheet molding compound) composite materials; (c) hollow polymer nanospheres are used in damping materials; (d) hollow polymer nanospheres are used in automotive sealants; (e) carbon fiber composite materials, chassis armor, special putty and other materials are also the application paths of hollow polymer nanospheres in lightweight automobiles.
[0043] (4) Application in adhesives
[0044] There are many types of adhesives with different components, including organic silicone adhesives, polyurethane adhesives, epoxy adhesives, EVA (ethylene vinylacetate copolymer adhesives, ethylene-vinyl acetate copolymer) adhesives, etc. Their base materials are mostly various types of resins. The application of hollow polymer nanoparticles in adhesives mainly has the following ways: (a) hollow polymer nanoparticles are used in special structural adhesives; (b) hollow polymer nanoparticles are used in bonding and packaging adhesives.
[0045] (5) Application in 5G communications
[0046] PCB (printed circuit board) is the foundation of 5G wireless communication equipment. To develop high-performance, high-frequency, low-dielectric PCB products, it is necessary to select resin matrix and fiber reinforcement materials with low dielectric constant and low dielectric loss factor. The hollow polymer nanospheres contain gas, and the dielectric constant of the gas is close to 1. With the polystyrene shell, the dielectric constant of the hollow polymer nanospheres is extremely low, which can effectively improve the dielectric properties of the material. At the same time, its advantages such as light weight, low thermal conductivity, non-toxicity, non-flammability, good chemical stability, and high dispersion improve the material's impact resistance, creep resistance, heat resistance, dimensional stability, insulation performance, rigidity, and stress damping. Therefore, hollow polymer nanospheres are a must-have filler for copper-clad laminate substrate materials for PCB substrates in the 5G era.
[0047] (6) Application in agricultural film and plastic film
[0048] Hollow polymer nanospheres as opening agents for plastic films can solve the problem of opening agents accumulating on the film surface, achieve better opening and smoothness for the film, improve the processing performance of the film without affecting the transparency of the film. Hollow polymer nanospheres as functional additives for film products can effectively reduce the dielectric constant of the film in the communication field; they have good heat insulation and thermal insulation effects when used in the construction field as glass films; and they can improve the preservation performance when used in cling film.
[0049] (7) Application in the environmental protection industry
[0050] Hollow polymer nanospheres are combined with ceramic materials as special pore-forming fillers and can be used in a variety of scenarios including aircraft and industrial exhaust gas treatment.
[0051] (8) Application in the medical industry
[0052] Hollow polymer nanospheres have many advantages and are very suitable for the medical and health industry to improve the performance of existing technologies, such as ultrasound enhancement, drug delivery, interventional surgery, embolism occlusion, bio-imaging, in vitro testing, medical devices, stent materials, catheter materials, etc.
[0053] (9) Application in sports goods and other industries
[0054] Taking advantage of the light weight of hollow polymer nano-microspheres, when preparing composite sports goods, adding hollow polymer nano-microspheres can not only reduce the amount of organic matter used and thus reduce VOC (volatile organic compounds) emissions, but also make the sports goods have stable size standards, wear resistance, light weight, good weather resistance, and are more conducive to athletes achieving good results. Such as lightweight basketball boards (low-density SMC products), lightweight water skis (the main material is a panel + composite foam sandwich structure), snowboards (HGM modified engineering plastics), etc.
[0055] (10) Application in emulsion explosives industry
[0056] After special surface treatment, the hollow polymer nanospheres can be closely combined with the oil film of the emulsion explosives, floating them and acting as stabilizers. When detonated by the outside world, each hollow polymer nanosphere is adiabatically compressed and the local temperature rises rapidly. When the temperature is high enough, it will cause intense exothermic chemical reactions such as oil phase combustion and oxidant decomposition, which plays a sensitizing role, greatly improving the detonation performance of the explosives and significantly improving the storage stability.
[0057] (11) Application in the green building materials industry
[0058] The application of hollow polymer nanospheres in the green building materials industry mainly includes the following ways: (a) hollow polymer nanospheres are used in thermal insulation coatings; (b) hollow polymer nanospheres are used in composite doors and windows; (c) hollow polymer nanospheres are used in artificial marble; (d) hollow polymer nanospheres are used in engineering wood, furniture, bathroom, etc.
[0059] (12) Application in electrical energy and transportation industries
[0060] The applications of hollow polymer nanospheres in the electrical energy and transportation industries are mainly as follows: (a) electric meter boxes, electrical cabinets, switch boxes; (b) new energy vehicle charging piles, battery boxes; (c) train window frames, bathroom components, bathrooms, wall panels, wash basins, shower trays, seats, coffee table tops, carriage wall panels, roof panels, electronic components, switch equipment, etc.
[0061] (13) Application in other areas
[0062] In addition to the above-mentioned main application directions, hollow polymer nanospheres also have broad application prospects in the fields of functionalized polymer microbead products, preparation of thermal, optical, electrical, absorbing, shielding and other materials, composite poles and towers, silicone rubber products, wind turbine blades, liquid crystal display spacer materials, medical immunoassays, biofunctional materials, absorbing materials, 3D printing materials, liquid metal materials, photocatalyst carrier materials, etc.
[0063] The hollow polystyrene microspheres of the present invention have the characteristics of low density, large specific surface area, adjustable hollowness and high load capacity. As mentioned above, they can be widely used in catalyst carriers, thermal insulation and sound insulation materials, optoelectronic materials, magnetic materials, drug microcapsule materials, aerospace, oil extraction, ocean exploration, communications, ships, automobiles, rail transportation, building materials, chemicals, electronics, medical treatment, environmental protection, cosmetics, sporting goods and other fields.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] (1) The present invention designs and functionally modifies the surface of polystyrene microspheres, adds glycidyl methacrylate during the polymerization process, and makes the surface of the microspheres contain a large number of epoxy groups and hydroxyl groups, which have good hydrophilicity and achieve the purpose of adjusting the polarity of the microsphere surface; some epoxy groups gradually cross-link during the hydrolysis process of the microsphere surface, which can increase the organic solvent resistance of the microspheres, and add nutritional active substances to the reaction solution, so that during the preparation process of the microspheres, the hydrophilic polymethacrylate glycidyl methacrylate is preferentially distributed on the outside of the microspheres, and the fat-soluble polystyrene is more distributed inside the microspheres, and finally synthesizes a microsphere with a core-shell structure; when the microspheres are soaked and swollen in an organic solvent, the internal polystyrene is easily dissolved, thereby realizing the hollowing of the microspheres, and obtaining a hollow polymer microsphere. In addition, since the functional groups on the surface of the microspheres can be coupled with most biological molecules through reactions, they can be widely used in the biomedical field.
[0066] (2) The functionalized hollow polymer microspheres prepared in the present invention have a large internal space, can encapsulate more functional substances, and have good stability; at the same time, the prepared hollow polymer microspheres have uniform particle size, no depressions or damage on the surface, can effectively encapsulate functional substances, and are not prone to leakage.
[0067] (3) The preparation method of the present invention is simple and controllable. The particle size of the microspheres and the pore size of the inner core can be controlled by adjusting process parameters such as the ratio of styrene monomer to functional monomer, initiation temperature, amount and type of initiator, amount of active ingredient, amount and type of organic solvent, thereby realizing the preparation concept of controllable morphology and controllable size. At the same time, the preparation conditions are easy to achieve, which is conducive to process scale-up research and easy to realize industrial production.
[0068] (5) The hollow polymer microspheres obtained by the present invention have good sphericity, no surface depressions, uniform particle size, high surface area and low density. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings in this description are only embodiments of the present invention.
[0070] Figure 1 This is a transmission electron micrograph of the solid polymer microspheres prepared in Example 1 of the present invention;
[0071] Figure 2 This is a transmission electron micrograph of the hollow polymer microspheres after swelling treatment prepared in Example 1 of the present invention;
[0072] Figure 3 This is a scanning electron microscope image of the solid polymer microspheres prepared in Example 1 of the present invention;
[0073] Figure 4 This is a scanning electron microscope image of the hollow polymer microspheres after swelling treatment prepared in Example 1 of the present invention;
[0074] Figure 5 The particle size and distribution diagram of the hollow polymer microspheres after swelling treatment prepared in Example 1 of the present invention;
[0075] Figure 6 The morphology of the hollow spheres in Example 4 of the present invention when the initiator temperature is 73° C. and 70° C. respectively;
[0076] Figure 7 The morphology of the hollow polymer microspheres prepared in Example 22 of the present invention at different solvent ratios and different swelling times is shown;
[0077] Figure 8 This is a diagram showing the coupling effect of microspheres of Example 27 of the present invention and a dye containing an amino group;
[0078] Fig. 9 This is a color comparison chart of blank polystyrene microspheres and microspheres of Example 27 of the present invention in a test tube. DETAILED DESCRIPTION
[0079] Embodiments of the present invention are described below. Examples of the embodiments are shown in the accompanying drawings. The embodiments described with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but are not to be construed as limiting the present invention.
[0080] Example 1
[0081] A method for preparing surface functionalized hollow polymer microspheres, comprising the following steps:
[0082] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 100 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensation water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70 ° C at room temperature. After reacting for 8 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 5 minutes, and the upper liquid was discarded by centrifugation. Then, it was alternately centrifuged and washed once with ethanol and water to obtain surface functionalized hollow polymer microspheres.
[0083] The products of Example 1 were subjected to transmission electron microscopy (TEM) testing on a HT7700 transmission electron microscope produced by Hitachi, Japan. The prepared polymer microspheres were diluted 1000 times and then dropped onto a copper support mesh covered with a carbon film. After being naturally dried at room temperature, the test results were as follows: Figure 1-2 ,in, Figure 1 This is a transmission electron microscope image of solid polymer microspheres before swelling treatment. It can be seen that the solid microspheres are regular spheres with a diameter of about 275nm. Figure 2 This is the transmission electron micrograph of the prepared hollow polymer microspheres after swelling treatment. It can be seen that after swelling, hollow polymer microspheres with intact surfaces are obtained. The shape is still spherical, and there are no depressions or damage on the surface, indicating that the polymer microspheres basically do not undergo morphological changes in tetrahydrofuran solvent. The measured diameter is about 270 nm.
[0084] The products related to Example 1 were subjected to scanning electron microscope (SEM) testing: the test was conducted on an Ultra 55 field emission scanning electron microscope from Zeiss, Germany. The synthetic polymer microsphere emulsion was diluted 1000 times and then dripped onto a silicon wafer and dried naturally at room temperature. Since the conductivity of polymer materials is poor, the samples were subjected to gold ion sputtering treatment before injection to prevent charge accumulation. The results are shown in Table 1. Figure 3-4 ,in Figure 3 This is a scanning electron microscope image of solid polymer microspheres before swelling treatment. It can be seen that the solid microspheres are regular spheres. Figure 4 The scanning electron microscope image of the prepared hollow polymer microspheres after swelling treatment shows that the shape is still spherical after swelling, and there are no depressions or damage on the surface, which also shows that the polymer microspheres basically do not change their morphology in tetrahydrofuran solvent.
[0085] The particle size and distribution test of the products related to Example 1 was performed: the hollow polymer microsphere solution was diluted 1000 times with deionized water and placed in a cuvette. The particle size of the hollow microspheres was measured at 25°C using a Zetasizer ZS-90 from Malvern, UK. The excitation light used in the instrument test was 633nm red light, the angle between the incident light and the detector was 90°, the insulation time was set to 2min during the test, and the zeta potential test temperature was 25°C. The particle size distribution of the hollow polymer microspheres is shown in FIG. Figure 5 As shown, it can be seen that the sizes of the microspheres are basically consistent, the particle size distribution deviation coefficient is 0.05, and they are monodisperse.
[0086] Example 2
[0087] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 10 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensation water was turned on and heated to 70 ° C at room temperature. After reacting for 16 hours, the reaction solution became milky white. The emulsion and acetone were mixed at a volume ratio of 1:5 for 10 minutes, and the upper layer of liquid was discarded by centrifugation. Subsequently, the microspheres were washed by centrifugation with ethanol and water respectively to obtain hollow polymer microspheres with a particle size of 254 nm and intact surface.
[0088] Example 3
[0089] 3 mL of styrene and 3 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensation water was turned on and heated to 70 ° C at room temperature. After reacting for 16 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper layer of liquid was discarded by centrifugation. Then, the microspheres were washed by centrifugation with water to obtain hollow polymer microspheres with a particle size of 322 nm and intact surface.
[0090] Example 4
[0091] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensation water was turned on and heated to 73 ° C at room temperature. After reacting for 10 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper layer of liquid was discarded by centrifugation. Then, the microspheres were washed by centrifugation with water to obtain hollow polymer microspheres with a particle size of 259 nm and intact surfaces.
[0092] According to the relevant parameters, as the polymerization temperature of this embodiment increases, the polymerization between the monomers is more inclined to random copolymerization. When the initiation temperature reaches 73°C, the reference Figure 7 The right figure shows that the hollow microspheres prepared at 73°C have a lower degree of hollowness (compared with the left figure at 70°C, the cavity size is significantly reduced). After analysis, it is found that at higher temperatures, a large amount of initiators decompose at the same time, the reaction is violent, and tends to random polymerization. There is no obvious difference in the composition of the inside and outside of the microspheres, and a hollow structure cannot be formed.
[0093] Example 5
[0094] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium bromide and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensation water was turned on and heated to 70 ° C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper layer of liquid was discarded by centrifugation. Then, the microspheres were washed by centrifugation with water to obtain hollow polymer microspheres with a particle size of 253 nm and intact surface.
[0095] Example 6
[0096] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of potassium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70 ° C at room temperature. After reacting for 8 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper liquid was centrifuged and discarded. Then, it was centrifuged and washed with water to obtain hollow polymer microspheres with a particle size of 254 nm and intact surface.
[0097] Example 7
[0098] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium chloride, 5 mg of amino acid and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 4 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper liquid was discarded by centrifugation. Subsequently, the mixture was washed alternately by centrifugation with ethanol and water, respectively, to obtain hollow polymer microspheres with a particle size of 264 nm and intact surface.
[0099] Example 8
[0100] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 10 mg of sodium chloride, 5 mg of amino acids, 5 mg of vitamins and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper liquid was discarded by centrifugation. Subsequently, it was alternately centrifuged and washed once with ethanol and water to obtain hollow polymer microspheres with a particle size of 250 nm and intact surface.
[0101] Example 9
[0102] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 3 mg of calcium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper liquid was discarded by centrifugation. Subsequently, the mixture was alternately centrifuged and washed once with ethanol and water to obtain hollow polymer microspheres with a particle size of 254 nm and intact surface.
[0103] Example 10
[0104] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 300 mg of potassium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper layer of liquid was discarded by centrifugation. Subsequently, the mixture was alternately centrifuged and washed once with ethanol and water to obtain hollow polymer microspheres with a particle size of 333 nm and intact surface.
[0105] Embodiment 11
[0106] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 300 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper layer of liquid was discarded by centrifugation. Subsequently, the mixture was alternately centrifuged and washed once with ethanol and water to obtain hollow polymer microspheres with a particle size of 423 nm and intact surface.
[0107] Example 12
[0108] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of sodium persulfate, 100 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper layer of liquid was discarded by centrifugation. Subsequently, the mixture was washed alternately by centrifugation with ethanol and water, respectively, to obtain hollow polymer microspheres with a particle size of 265 nm and intact surface.
[0109] Example 13
[0110] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 400 mg of potassium persulfate, 50 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper liquid was discarded by centrifugation. Subsequently, the mixture was washed alternately by centrifugation with ethanol and water, respectively, to obtain hollow polymer microspheres with a particle size of 285 nm and intact surface.
[0111] Embodiment 14
[0112] 3 mL of styrene and 1.2 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 10 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper liquid was discarded by centrifugation. Subsequently, the mixture was alternately centrifuged and washed once with ethanol and water to obtain hollow polymer microspheres with a particle size of 244 nm and intact surface.
[0113] Embodiment 15
[0114] 5 mL of styrene and 3 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper liquid was discarded by centrifugation. Subsequently, the mixture was washed alternately by centrifugation with ethanol and water, respectively, to obtain hollow polymer microspheres with a particle size of 298 nm and intact surface.
[0115] Example 16
[0116] 4 mL of styrene and 2 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensation water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper liquid was discarded by centrifugation. Subsequently, the mixture was alternately centrifuged and washed once with ethanol and water to obtain hollow polymer microspheres with a particle size of 281 nm and intact surface.
[0117] Embodiment 17
[0118] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 200 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper liquid was discarded by centrifugation. Subsequently, the mixture was washed alternately by centrifugation with ethanol and water, respectively, to obtain hollow polymer microspheres with a particle size of 215 nm and intact surface.
[0119] Embodiment 18
[0120] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 250 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper layer of liquid was discarded by centrifugation. Subsequently, the mixture was alternately centrifuged and washed once with ethanol and water to obtain hollow polymer microspheres with a particle size of 224 nm and intact surface.
[0121] Embodiment 19
[0122] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 400 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper liquid was discarded by centrifugation. Subsequently, the mixture was alternately centrifuged and washed once with ethanol and water to obtain hollow polymer microspheres with a particle size of 239 nm and intact surface.
[0123] Embodiment 20
[0124] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 500 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper layer of liquid was discarded by centrifugation. Subsequently, the mixture was alternately centrifuged and washed once with ethanol and water to obtain hollow polymer microspheres with a particle size of 302 nm and intact surface.
[0125] Embodiment 21
[0126] 10 mL of styrene and 6 mL of glycidyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and the inert gas was introduced for 15 minutes. Then, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. The emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, and the upper layer of liquid was discarded by centrifugation. Subsequently, the mixture was alternately centrifuged and washed once with ethanol and water to obtain hollow polymer microspheres with a particle size of 475 nm and intact surface.
[0127] Comparative Examples 1-14
[0128] Styrene and glycidyl methacrylate in different ratios were added to a 250 mL three-necked flask, 110 mg of potassium persulfate and 100 mL of deionized water were added, a certain amount of mineral salt was added or not, mechanical stirring was started and the speed was set to 350 rpm, condensation water was turned on, inert gas was introduced for 15 minutes, and then heated to the set temperature at room temperature. After reacting for 12 hours, the reaction solution became milky white, the emulsion and tetrahydrofuran were mixed in a volume ratio of 1:5 and swelled for 10 minutes, and then the upper layer of liquid was discarded by centrifugation, and then ethanol and water were alternately centrifuged and washed once; the specific parameters of each comparative reaction are shown in Table 1, and the obtained polymer microspheres were tested by transmission electron microscopy to observe the particle size and swelling results, as shown in Table 1.
[0129] Table 1 Preparation parameters and swelling results of polymer microspheres prepared in Comparative Examples 1-14
[0130]
[0131] In the field of polymer microspheres, the polymer chain of the microspheres without adding functional monomers is a linear structure, which is difficult to stably exist in high-concentration organic solvents; it can be seen from Comparative Example 8 in Table 1 that when the addition amount of styrene St is 0, the prepared polymer microspheres have excellent stability, no change in organic solvents, and solid microspheres can be obtained; when a higher amount of glycidyl methacrylate (GMA for short) is added, the synthesized polymer microspheres can also stably exist for a long time in high-concentration organic solvents in the absence of a cross-linking agent, and solid microspheres can be obtained, namely Comparative Examples 3, 4, and 5; GMA dosage at a suitable ratio can make the microspheres in a hollow structure, but further reducing the GMA dosage will cause the microspheres to be damaged or dissolved to a greater extent in organic solvents, that is, the hollow polymer microspheres are "not firm". By adding an appropriate amount of sodium chloride and other mineral salts to the reaction solution, hollow polymer microspheres with intact surfaces after swelling can be obtained. It is found that the addition of mineral salts will push up the limit of the amount of GMA used for hollow polymer microspheres. At the same time, increasing the amount of mineral salts will also increase the hollowness of the microspheres. However, increasing the amount of GMA will reduce the hollowness of the microspheres, and excessive mineral salts will cause the microspheres to adhere during the preparation and swelling process. When the initiation temperature reaches 77°C and 81°C, the microspheres are not hollowed out during the swelling process of organic solvents. At the same time, when the initiation temperature is reduced, precipitation will occur during the preparation of the microspheres, and hollow microspheres and solid microspheres will coexist after swelling.
[0132] Comparative Example 15
[0133] 3 mL of styrene and 1.8 mL of hydroxyethyl methacrylate were added to a 250 mL three-necked flask, and 110 mg of potassium persulfate, 30 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensation water was turned on, and an inert gas was introduced for 15 minutes. The mixture was heated to 70°C at room temperature and reacted for 12 hours. After the emulsion and tetrahydrofuran were mixed at a volume ratio of 1:5 for 10 minutes, the obtained polymer microspheres agglomerated and no qualified target product was obtained.
[0134] Comparative Example 16
[0135] The preparation method is the same as that of Comparative Example 15, except that the hydroxyethyl methacrylate monomer is replaced with ethylene glycol dimethacrylate. The resulting polymer microspheres agglomerate and no qualified target product is obtained.
[0136] Comparative Example 17
[0137] The preparation method is the same as that of Comparative Example 15, except that the hydroxyethyl methacrylate monomer is replaced by acrylic acid. The resulting polymer microspheres are dissolved and no qualified target product is obtained.
[0138] Comparative Example 18
[0139] The preparation method is the same as that of Comparative Example 15, except that the hydroxyethyl methacrylate monomer is replaced with methacrylic acid. The resulting polymer microspheres agglomerate and no qualified target product is obtained.
[0140] It can be seen from the above-mentioned relevant comparative examples that the present invention successfully prepared hollow polymer microspheres containing epoxy groups on the surface by adjusting process parameters such as the amount of styrene, the type and amount of functional monomers, the initiation temperature, the type and amount of initiator, the type and amount of active ingredients, and the amount and type of organic solvents; in the present invention, the functional monomer GMA and the active ingredient are indispensable. When the content of the functional monomer is low, the microspheres are difficult to stably exist in a high concentration of organic solvents, and hollow polymer microspheres with uniform particle size cannot be obtained.
[0141] Embodiment 22
[0142] The solid polymer microsphere emulsion prepared in Example 1 was mixed with tetrahydrofuran at a volume ratio of 1:1, 1:3, 1:5, and 1:10 and swollen for 5 min, 20 min, 12 h, and 24 h. The upper liquid was discarded by centrifugation, and transmission electron microscopy was performed without centrifugation. The results are shown in FIG. Figure 6 .
[0143] like Figure 6 As shown in the figure, when the microspheres are swollen with a higher content of tetrahydrofuran (the volume ratio of microsphere emulsion to tetrahydrofuran is 1:5 and 1:10, respectively), there is no obvious difference in the morphology of the microspheres swollen for 20 minutes, 12 hours, and 24 hours, and all have a high monodispersity. In addition, when the microspheres are swollen with a lower content of tetrahydrofuran (the volume ratio of microsphere emulsion to tetrahydrofuran is 1:1 and 1:3, respectively), adhesion occurs between the microspheres, mainly because the polystyrene swollen from the inside of the microspheres cannot be effectively dissolved at a low tetrahydrofuran content, and it adheres to the surface of the microspheres, causing the microspheres to agglomerate with each other.
[0144] Embodiment 23
[0145] The hollow polystyrene microspheres prepared by the preparation method of Example 1 were added to PBS buffer (8 g NaCl, 0.2 g KCl, 0.24 g KH2PO4, 1.44 g Na2HPO4) containing amoxicillin, and stirred at 200 rpm at 35°C for 24 h. The drug concentration was 100 μg / mL. The results showed that the drug loading was 2 times higher than that of the solid spheres.
[0146] The hollow polystyrene microspheres of the present invention are smooth in appearance, good in sphericity, uniform in particle size, and excellent in swelling performance. They have a high drug loading capacity and a sustained-release effect. Meanwhile, the hollow polystyrene microspheres are biodegradable, non-toxic and harmless, and are an ideal drug carrier.
[0147] Example 24 Effect of some reagent dosages on hollow polymer microspheres
[0148] In soap-free emulsion polymerization systems, the amount and concentration of monomers and other reagents directly affect the performance of microspheres. While ensuring sufficient performance of the microspheres, it is crucial to scale up the reaction to obtain higher yields in the field of large-scale production.
[0149] The experiment was designed and carried out according to Example 1, except that the dosage of some reagents was adjusted according to Table 2, wherein the active ingredient of the additive was an aqueous solution containing 50 mg of sodium nitrate; as shown in Table 2, when the concentration of the monomer and other reagents was low (Entry 1), the particle size of the microspheres was small, and the microspheres were solid after swelling. This may be due to the fact that there is no distinct boundary between the distribution of the two polymer chains inside the microspheres. When the volume of the microspheres is small, the uneven distribution of the polymer chains constituting the microspheres is not enough to make most of its internal components PS polymer chains, and the internal structure cannot be dissolved in THF solvent, so it is synthesized into a solid structure.
[0150] When the overall content of monomers and other reagents increases (Table 2, entries 2 to 9), the particle size of the microspheres increases continuously, and the hollowness of the microspheres increases accordingly after swelling. The microspheres are still spherical in shape and stable for a long time, and no agglomeration occurs within 1000nm (Entries 2 to 8); when the particle size increases further, some agglomeration occurs (Entry 9).
[0151] Table 2 Effect of some reagent dosage on hollow polymer microspheres
[0152]
[0153] Embodiment 25
[0154] 3 mL of styrene and 3 mL of glycidyl methacrylate were added to a 500 mL three-necked flask, and 200 mg of ammonium persulfate, 20 mg of sodium chloride and 200 mL of deionized water were added. The mechanical stirring was started and the speed was set to 150 rpm. The condensing water was turned on, and the inert gas nitrogen / argon (volume ratio of 1:1) was introduced for 20 minutes. The mixture was heated to 70°C at room temperature. After reacting for 6 hours, the reaction solution became milky white. The emulsion was mixed and stirred with toluene and ethyl acetate in a volume ratio of 1:3:1 for 5 minutes, and the upper liquid was discarded by centrifugation. The mixture was then centrifuged and washed with ethanol and water, respectively, to obtain hollow polymer microspheres with a particle size of 168 nm and intact surfaces.
[0155] Embodiment 26
[0156] 30 mL of styrene and 18 mL of glycidyl methacrylate were added to a 2000 mL four-necked flask, and 1000 mg of sodium persulfate, 200 mg of sodium chloride, 100 mg of potassium carbonate, 100 mg of sodium bisulfate and 1000 mL of deionized water were added. The mechanical stirring was started and the speed was set to 300 rpm. The condensation water was turned on, and the inert gas argon was introduced for 30 minutes. The mixture was heated to 70 ° C at room temperature. After reacting for 8 hours, the reaction solution became milky white. The emulsion and toluene and acetone were mixed and stirred at a volume ratio of 1:1:4 for 8 minutes, and the upper liquid was discarded by centrifugation. Subsequently, the mixture was centrifuged and washed with ethanol and water, respectively, to obtain hollow polymer microspheres with a particle size of 260 nm and intact surface.
[0157] Example 27 Coupling experiment of hollow polymer microspheres and amino-containing dyes
[0158] Take a small amount of amino-containing dye (4-(6-methyl-1,2,4,5-tetrazine-3-yl)phenyl)methylamine hydrochloride and dissolve it in 2 mL of deionized water. Then divide it evenly into two centrifuge tubes, add 0.5 mL of microsphere emulsion to each centrifuge tube and shake well (as shown in Table 1). Figure 8 As shown, the control group on the left added ordinary polystyrene microspheres, which were polymerized with styrene as a monomer and did not contain other functional monomers; the experimental group on the right added hollow microspheres obtained in Example 1), and after overnight reaction, centrifugation was performed, and the supernatant was discarded, and then centrifuged and washed twice with deionized water; the dye (pink) used in this experiment contains an amino structure and can undergo a nucleophilic reaction with an epoxy group. Fig. 9 Compared with blank polystyrene microspheres (colorless, sample at the bottom of left tube 1), it was found that the microspheres of the present invention were successfully dyed (pink, sample at the bottom of right tube 2), which further proved that there were epoxy groups on the surface of the microspheres and that they could undergo coupling reaction smoothly with the amino groups.
[0159] Example 28 Preparation of luminescent hollow polymer microspheres
[0160] Weigh 0.2 g of Eu(III) complex Eu(TTA)3(TPPO )2 , dissolved in 20 mL of acetone to prepare an acetone solution of Eu(III) complex with a concentration of 1 g / 100 μL, take 20 μL of Eu(III) complex acetone solution in a 2 mL glass bottle, then add 180 μL of acetone solution and mix well, then add 600 μL of deionized water, mix well, add 200 μL of hollow microsphere emulsion with a solid content of 0.5% (obtained in Example 26), mix well, centrifuge the emulsion, discard the supernatant, add deionized water and ultrasonically disperse, repeat washing again and store at room temperature;
[0161] The hollow microspheres prepared by the present invention are stronger in dye loading than conventional polymer microspheres, because the hollow microspheres prepared by the present invention contain more cavities inside to enhance the ability to adsorb dyes, and there are more hydrophilic polymer chains outside to protect the oil-soluble Eu (III) complex dye. Tests have found that under the excitation of 365nm ultraviolet light, the luminescent hollow microspheres emit characteristic peaks of Eu, wherein the main peak is bright red light at 615nm.
[0162] Example 29: Simple wet chemical preparation of luminescent hollow polymer microspheres
[0163] 3 mL of styrene and 1.8 mL of glycidyl methacrylate were added to a 1000 mL three-necked flask, and 110 mg of sodium persulfate, 100 mg of sodium chloride and 100 mL of deionized water were added. The mechanical stirring was started and the speed was set to 350 rpm. The condensed water was turned on, and after the inert gas was introduced for 15 minutes, it was heated to 70°C at room temperature. After reacting for 12 hours, the reaction solution became milky white. 300 mL of tetrahydrofuran solution containing 150 mg of the complex Eu(TTA)3(TPPO)2 was added, and the emulsion was centrifuged after stirring and mixing. After discarding the supernatant, deionized water was added and ultrasonically dispersed. After repeated washing, it was stored at room temperature to obtain luminescent hollow polymer microspheres with a particle size of 265 nm and complete surface.
[0164] The preparation method of the present invention is simple and directly integrates the synthesis of hollow polymer microspheres and the loading of luminescent dyes. Tests have shown that under the excitation of 365nm ultraviolet light, the prepared luminescent hollow microspheres emit characteristic peaks of Eu, wherein the main peak is bright red light at 615nm.
[0165] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing surface functionalized hollow polymer microspheres, characterized in that: The specific steps include: (1) stirring styrene, functional monomers, initiators, active ingredients and deionized water to obtain an emulsion for standby use; (2) The emulsion is swollen with an organic solvent, and the precipitate obtained after centrifugation is the surface functionalized hollow polymer microspheres.
2. The method for preparing surface functionalized hollow polymer microspheres according to claim 1, characterized in that: The mass ratio of the active ingredient to the deionized water in step (1) is 0.003-0.3:100; The volume ratio of the styrene, the functional monomer and the deionized water is 3-10:1.2-6:100; The mass ratio of the initiator to the deionized water is 0.05-0.4:
100.
3. The method for preparing surface functionalized hollow polymer microspheres according to claim 1, characterized in that: The reaction temperature in step (1) is 63-75°C, the reaction time is 4-16h, and the stirring speed is 150-600rpm.
4. The method for preparing surface functionalized hollow polymer microspheres according to claim 1, characterized in that: The active ingredients in step (1) include mineral salts and / or biomacromolecules; The functional monomer is glycidyl methacrylate; The initiator is any one of potassium persulfate, sodium persulfate and ammonium persulfate.
5. The method for preparing surface functionalized hollow polymer microspheres according to claim 1, characterized in that: In step (2), the volume ratio of the emulsion to the organic solvent is greater than 1, and the swelling time is greater than 1 min.
6. The method for preparing surface functionalized hollow polymer microspheres according to claim 1, characterized in that: The organic solvent in step (2) is at least one of tetrahydrofuran, acetone, ether, ethyl acetate, cyclohexane, toluene, xylene and trimethylbenzene.
7. The method for preparing surface functionalized hollow polymer microspheres according to claim 4, characterized in that: The mineral salt includes at least one of calcium salt, phosphorus salt, magnesium salt, potassium salt, sodium salt, iron salt, zinc salt, copper salt, manganese salt, iodine salt, selenium salt and molybdenum salt; The biomacromolecules include at least one of amino acids, nucleotides, polysaccharides, vitamins and proteins.
8. A surface functionalized hollow polymer microsphere obtained by the preparation method according to any one of claims 1 to 7.
9. The surface functionalized hollow polymer microsphere according to claim 8, characterized in that: The particle size of the hollow polymer microspheres is 100-1000nm.
10. Use of a surface functionalized hollow polymer microsphere obtained by the preparation method according to any one of claims 1 to 7 in the preparation of catalysts, thermal and sound insulation materials, optoelectronic materials, magnetic materials, and drug microcapsule materials.
Citation Information
Patent Citations
Method of preparing micron-level magnetic polymer micro-sphere by polarity seed swelling method
CN101058614A
Preparation method of surface-functionalized, micron-sized, porous, paramagnetic and spherical resin particle
CN106622172A
Conductive microsphere with surface protrusion structure as well as preparation method and application of conductive microsphere
CN115109277A
DNA-immobilized microspheres and a process for purifying a DNA-transcription-controlling factor using the same
US5122600A
Microsphere containing glycidyl methacrylate covered polymer and spacer coupled compound for isolating substances
US6545132B1